Strategies to increase vitamin C in plants: from plant defense perspective to food biofortification - Locato, Vittoria; Cimini, Sara; De Gara, Laura (Frontiers in Plant Science, 2013)
Vitamin C participates in several physiological processes, among others, immune stimulation, synthesis of collagen, hormones, neurotransmitters, and iron absorption. Severe deficiency leads to scurvy, whereas a limited vitamin C intake causes general symptoms, such as increased susceptibility to infections, fatigue, insomnia, and weight loss. Surprisingly vitamin C deficiencies are spread in both developing and developed countries, with the latter actually trying to overcome this lack through dietary supplements and food fortification. Therefore new strategies aimed to increase vitamin C in food plants would be of interest to improve human health. Interestingly, plants are not only living bioreactors for vitamin C production in optimal growing conditions, but also they can increase their vitamin C content as consequence of stress conditions. An overview of the different approaches aimed at increasing vitamin C level in plant food is given. They include genotype selection by “classical” breeding, bio-engineering and changes of the agronomic conditions, on the basis of the emerging concepts that plant can enhance vitamin C synthesis as part of defense responses.